Modeling pastille products recipe using unconventional raw materials in accordance with predetermined quality indicators - Соколовська, Олена Олександрівна (Technology audit and production reserves, 2016)
The article is devoted to the spread of diabetes and iodine-deficient condition among population. To expand the range of products with reduced carbohydrate loading and rich in minerals, including iodine, the author proposed rationalization of pastille products recipe using new raw material, namely pastille with an aqueous extract of stevia, stevioside, elamin under predetermined quality parameters, which was the aim of this article. Pastille is a traditional confectionery of CIS region, in the range of foreign countries these products are available. However, its calorie content is quite high, due to high content of white sugar and restricts the use of products. Pastille recipe composition was rationalized through mathematical modeling by using new raw material for partial removal of the mass fraction of white sugar with simultaneous iodine fortification of products. To achieve this aim it was defined concentration of agar Cag. = 3 % and water extract of stevia Cwes = 1,0 % during cooking sugar syrup to reduce a mass fraction of white sugar without loss of quality characteristics of semi-finished products. In parallel it was set range of rational concentration for stevioside Sstev = 1,5 ... 2,5 % by mechanical impact during τ = 5 ... 7 · 60 s by replacing white sugar. The results helped to rationalize the recipe ratio of components according to predetermined quality parameters for pastille using unconventional materials: x1 = 14,5; x2 = 1,2; x3 = 0,12; x4 = 10,0, which is the recommended settings for pastille production candy.